2023
DOI: 10.1002/zoo.21749
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of cultural norms and behavioural beliefs about zoo animal behaviour, welfare, ethics and husbandry practices in a sample of the international zoo community

Abstract: Beliefs influence the intentions of people to behave in certain ways towards animals. This study presents survey responses from 237 people working in zoos in China and Europe and describes their demographic characteristics. It explores their beliefs about zoo animal behaviour, welfare and ethical issues, and zoo practices, using a survey methodology. These beliefs may be influenced by individual demographic or cultural factors such as age, gender and region of employment, as well as experiential or situative '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Both Europe and North America had a greater number of keywords overall, despite Asia having a similar number of aquariums, suggesting cultural and societal ideology may play a role in how the public perceive welfare. When surveying Chinese and European zookeepers, Bacon et al [1] found that there was variation in welfare perception; it is possible a similar variation exists within the general public. This may also be reflected in the aquatic invertebrate comments, with corals having a greater representation in Asia than other regions due to their commercial importance for the region.…”
Section: Visitor Perceptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both Europe and North America had a greater number of keywords overall, despite Asia having a similar number of aquariums, suggesting cultural and societal ideology may play a role in how the public perceive welfare. When surveying Chinese and European zookeepers, Bacon et al [1] found that there was variation in welfare perception; it is possible a similar variation exists within the general public. This may also be reflected in the aquatic invertebrate comments, with corals having a greater representation in Asia than other regions due to their commercial importance for the region.…”
Section: Visitor Perceptionmentioning
confidence: 99%
“…By creating a positive environment, the ability to understand the animal better would result in overall standards improving [47]. The human factor of good animal welfare in collections was summarized by Bacon et al [1], and one of the key findings was that the aquarium should consider the wellbeing of their staff as a function of welfare. Aquarists have a large influence on the organisms that they care for, and if their welfare is compromised then potentially so are the animals.…”
Section: Aquarium Welfare Resourcesmentioning
confidence: 99%
See 3 more Smart Citations